Tazkirah-yi akābir-i Ahl-i Sunnat - Sharf Qādirī, Muḥammad ʻAbdulḥakīm (Silsilah-yi ishā'at / Maktabah Qādriyyah Jāmiʻah Nizāmiyyah Rizviyyah, 1976)
"Biographical dictionary of eminent Sunni scholars of the Indo-Pakistan subcontinent"--PL-480 copy.